ASSOCIATION BETWEEN SELF-PERCEIVED BODY IMAGE, A FITNESS AND LIFESTYLE OF TEENAGERS (Fiep Bulletin - online, 2014)
The present study aimed to associate the self-perception of body image, with physical fitness and the lifestyle of high school students. Was to sample 52 students in age group between 15 and 18 years. Three instruments were used for data collection: the FITNESSGRAM, the Escala de Evaluación de Insatisfacción Corporal en Adolescentes - EEICA and Social Interaction Questionnaire and Physical Education. The risk of developing cardiovascular disease is higher in girls because they presented the highest rate of skin folds, the boys considered being more physically active in childhood when, reflecting on the positive perception of body image. It was concluded that good physical fitness levels may have corroborated the positive self-perceived body image of adolescents focusing on lifestyle adopted by most physically active, as well as the enhancement of health information covered in Physical Education classes.
Keywords: Body image; Fitness; Lifestyle; Teenagers.